2018
DOI: 10.1039/c8cc01913d
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced ring-opening polymerisation of l-lactide via a photocaged superbase

Abstract: The phototriggered ring-opening polymerisation of l-lactide is demonstrated for the first time using a photocaged tetramethylguanidine. The catalytic activity of the free guanidine was also investigated, showing it to be active for the polymerisation of δ-valerolactone and ε-caprolactone in the presence of a thiourea cocatalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 40 publications
0
35
0
2
Order By: Relevance
“…The development of this new PBG also extended the application to polymerization methodologies incompatible with previously generated amines. Recently, Kuroishi and Dove demonstrated the use of a NPPOC‐TMG in the photoinduced ROP of l ‐lactide . The authors observed no polymerization occurring in the dark, whereas irradiation promoted the ROP, which demonstrated the excellent temporal control over the polymerization initiation provided by the use of NPPOC‐TMG.…”
Section: Photobase Generatorsmentioning
confidence: 99%
“…The development of this new PBG also extended the application to polymerization methodologies incompatible with previously generated amines. Recently, Kuroishi and Dove demonstrated the use of a NPPOC‐TMG in the photoinduced ROP of l ‐lactide . The authors observed no polymerization occurring in the dark, whereas irradiation promoted the ROP, which demonstrated the excellent temporal control over the polymerization initiation provided by the use of NPPOC‐TMG.…”
Section: Photobase Generatorsmentioning
confidence: 99%
“…New methodologies for photopolymerization will allow for nonacrylic based monomers to be used, which may offer alternatives that are better tolerated and inherently biodegradable. [91][92][93][94][95] All of these considerations offer an enticing opportunity to bring in vivo polymerization out of the realm of science fiction.…”
Section: Photopolymerizationmentioning
confidence: 99%
“…Diese schnelle Kinetik ermçglichte eine weitere Demonstration der räumlichen Kontrolle durch Photopatterning,d ie im Allgemeinen eine schnelle Bildung eines Netzwerks erfordert, um die Diffusion des Katalysators zu reduzieren und hohe Auflçsungen zu erzielen. [73] Die Autoren beobachteten keine Polymerisation im Dunkeln, während die Bestrahlung die ROPi nitiierte,w as die ausgezeichnete zeitliche Kontrolle über die Polymerisationsinitiierung durch den Einsatz von NPPOC-TMG demonstrierte.D arüber hinaus lieferte diese Methode schnellere Polymerisationsraten, einschließlich einer grçßeren Kontrolle über das Molekulargewicht als andere durch Licht ausgelçste ROPs, [20] und zwar ohne die Verwendung von schädlicher hochenergetischer UV-Strahlung. [72] Die Entwicklung dieses neuen PBG erweiterte auch die Anwendung auf Polymerisationsmethoden, die mit zuvor erzeugten Aminen nicht kompatibel sind.…”
Section: Carbamateunclassified
“…Kürzlich haben Kuroishi und Dove den Einsatz eines NPPOC-TMG in der photoinduzierten ROP von l-Lactid gezeigt. [73] Abschließend gewinnt unter den 3D-Fertigungstechniken die Zwei-Photonen-Polymerisation an Bedeutung, da diese Te chnik die Herstellung von komplexen 3D-Formen mit hoher Auflçsung und Grçßen unter 100 nm ermçglicht. Es ist zu erwähnen, dass solche 3D-Objekte bemerkenswerte Eigenschaften in photonischen, elektronischen und biomedizinischen Anwendungen haben.…”
Section: Carbamateunclassified